Evaluation of anaerobic threshold in non-pregnant and pregnant rats - NETTO,ALINE OLIVEIRA (2017)
ABSTRACT Several studies present different methodologies and results about intensity exercise, and many of them are performed in male rats. However, the impact of different type, intensity, frequency and duration of exercise on female rats needs more investigation. From the analysis of blood lactate concentration during lactate minimum test (LacMin) in the swimming exercise, the anaerobic threshold (AT) was identified, which parameter is defined as the transition point between aerobic and anaerobic metabolism. LacMin test is considered a good indicator of aerobic conditioning and has been used in prescription of training in different exercise modalities. However, there is no evidence of LacMin test in female rats. The objective was to determine AT in non-pregnant and pregnant Wistar rats. The LacMin test was performed and AT defined for mild exercise intensity was from a load equivalent to 1% of body weight (bw), moderate exercise as carrying 4% bw and severe intensity as carrying 7% bw. In pregnant rats, the AT was reached at a lower loading from 5.0% to 5.5% bw, while in non-pregnant the load was from 5.5% to 6.0% bw. Thus, this study was effective to identify exercise intensities in pregnant and non-pregnant rats using anaerobic threshold by LacMin test.